Integrative Leadership of Madrasah Heads and Its Implications for the Quality of Education at Madrasah - Holidin; Zamroni; Wahdatun Nisa (Al-Qalam Institue, 2026)
The leadership of madrasah heads is a strategic factor in determining the quality of education, especially in the context of Islamic education which requires the integration of religious values and academic competence. This study aims to understand the integrative leadership pattern of madrasah heads and its implications on the quality of Madrasah education. The method used was qualitative with a multisite study design, involving in-depth interviews, participatory observation, and documentation analysis. The results show that integrative leadership combines the roles of leader, manager, and supervisor, and involves innovative strategies, academic supervision, strengthening of a quality culture, and active participation of teachers and stakeholders. The head of the madrasah adjusts the approach according to the social, cultural, and resource context of each site. In conclusion, the effectiveness of leadership is determined by a combination of adaptive and contextual strategies and the holistic management of internal and external factors. This research makes a theoretical contribution by expanding the concepts of transformational leadership and TQM in Islamic education as well as practical contributions to the development of effective and sustainable madrasah management.